Analysis of Knowledge Factors and Activity Patterns on Stunting in Adolescents (Junior High School) through Nutritional Patterns in Bojonegoro Regency - Wulandari, Endah Sri; Kasmini Handayani, Oktavia Woro; Wijayanti, Yuni (Public Health Perspective Journal, 2021)
The problem of stunting is what illustrates the existence of chronic nutritional problems directly affecting health. Stunting in adolescents leads to decreased reproduction, increased risk of obesity, reduced concentration of learning, and degenerative diseases in the future. Adolescents need to obtain access to information and education about stunting. The purpose of this study analyzed the direct and indirect effect of knowledge factors and activity patterns of stunting in adolescents through nutritional patterns. This study was an observational analytic study with a cross-sectional design. The number of samples were 380 adolescents aged 10-15 years. The analysis of this study used path analysis. The results of this study showed that the activity pattern had a positive and significant effect directly on the incidence of stunting with a value of p = 0.048 and knowledge had a negative and significant effect directly on the incidence of stunting with a value of p=0.000. Furthermore, the activity patterns also have an indirect positive effect on the incidence of stunting through nutritional patterns, while knowledge has an indirect negative effect on the incidence of stunting through nutritional patterns. This showed that knowledge is the most influencing factor on the incidence of stunting in adolescents through nutritional patterns with a total value of the indirect effect of 1.27.